Controle de Hovenia dulcis utilizando extratos vegetais - Anchieta, Mylena Gonçalves (2022)
Conservation units aim to conserve the natural biodiversity of ecosystems, preserving fragments of Brazilian biomes. However, some of these units are threatened by the invasion of exotic species. Control actions are important to be developed to protect areas that play important role in society. In general, all plants have natural defense mechanisms that protect them from other plants and threats. These defense mechanisms are chemical and can be extracted from the plant matrix. In this sense, bioactive extracts have been used as an alternative to the use of chemical herbicides. Therefore, the objective of this work was to evaluate the efficiency of extracts from Psidium cattleianum, known as araçá, and Capsicum baccatum, known as dedo-de-moça pepper, in the control of Hovenia dulcis, known as uva-do-japão. Ultrasound-assisted extractions were performed with 20 g of mass of samples and 25.4 mL of distilled water. The effects of time (20 – 60 min), maximum power fraction (50 – 100%), and pulse cycle (0.3 – 0.7) on compound extraction activities were evaluated. To evaluate the effect of the extracts, preemergence (Cucumis sativus var. and Hovenia dulcis) and post-emergence (Hovenia dulcis) bioassays were performed. The results found in the bioassays show that the extracts of Capsicum baccatum had a higher inhibitory effect on the germination of cucumber seeds when compared with Psidium cattleianum. Based on this result, the extract was applied to Hovenia dulcis seeds. Although the extract did not completely inhibit germination, it presented an effect against the normal development of seedlings, including the aerial parts and roots. The post-emergence results of Hovenia dulcis had a slight effect on the plants, causing yellowing in some samples. The application of the extracts from dedo-de-moça pepper showed the action effects against the normal development of Hovenia dulcis.